ANALISA FAKTOR YANG MEMPENGARUHI HAKIM DALAM MENETAPKAN HUKUMAN PIDANA BAGI PENGGUNA NARKOBA DI BAWAH UMUR - Derry Angling Kesuma (Jurnal Kelola: Jurnal Ilmu Sosial, 2018)
Drug cases among teenagers show an increasing number, the cases handled by the courts are varied. This study is to analyze various factors that influence judges to determine the focus of punishment for drug abusers who are underage. This research is a qualitative research with a juridical-normative approach. The data used in the form of secondary data. Data were collected through interviews and literature study, the number of respondents in this study revealed 10 court judges who had handled drug cases committed by minors. From the results of research analysis, what is said that in deciding drug cases is under assessment by various factors, including: political influence, effect of law enforcement, and influence of public opinion and media.